The influence of socioemotional well-being on mental health among university students in Klang Valley, Malaysia - Abd Razak, Marini; Abd Karim, Aishah Hanim (Olympia International College, 2024)
This study examines the influence of socioemotional well-being (SEWB) on mental health among university students in the Klang Valley, Malaysia. SEWB, encompassing emotional regulation, social support, self-esteem, and resilience, is critical in buffering mental health challenges. Utilizing a quantitative ex-post facto design, this study evaluates SEWB dimensions Status, Situation, Power, and Self and their impact on mental health, focusing on the moderating effects of cultural and gender contexts. Results indicate that SEWB significantly correlates with mental health outcomes, with Status emerging as the strongest predictor, followed by Situation and Power. The findings align with Self-Determination Theory, emphasizing autonomy, competence, and relatedness as key psychological needs influencing mental well-being. Notably, gender differences reveal that female students experience stronger correlations between SEWB and mental health, suggesting a need for gender-sensitive mental health programs. The study contributes to understanding how SEWB supports mental health in a collectivist context, highlighting implications for culturally tailored mental health interventions in Malaysian universities.